Triplet-ground-state nonalternant nanographene with high stability and long spin lifetimes - Weixiang Zhou; Yiyang Fei; Yu-Shuang Zhang; Xiaohe Miao; Shang-Da Jiang; Junzhi Liu (Nature Communications)
Abstract High-spin carbon-based polyradicals exhibit significant potential for applications in quantum information storage and sensing; however, their practical application is hampered by limited structural diversity and chemical instability. Here, we report a straightforward synthetic and isolation method for synthesizing a nonalternant nanographene (1) with a triplet ground state. Moving beyond the classic m-xylylene scaffold for high-spin organic molecules, seven-five-seven (7–5–7)-membered rings are introduced to create stable high-spin diradicals with half-lives (t 1/2) as long as 101 days. Moreover, considering the spin relaxation of compound 1, with a spin–lattice relaxation time (T 1) of 53.55 ms and a coherence time (T m) of 3.41 μs at 10 K, the compound 1 shows great promise for applications in spin-based information retention and quantum computing.